Run on your new legs. 4 - Midori, Wataru (Yen Press, 2023)
Kikuzato is excited to continue training with his new custom running prosthesis, even though the worsening pandemic has forced schools to close. While the track and field club members need to find creative ways to train, Kikuzato also has to face being in close quarters with his father, who is now working from home.